INTEGRATING MULTICULTURAL CONTENT AND CANVA-BASED MULTIMODAL LEARNING TO IMPROVE EFL STUDENTS’ VOCABULARY MASTERY - Novita Anggraini; Nirwanto Maruf (University of Kuningan, 2026)
This study aimed to develop and evaluate multicultural-based vocabulary learning materials using Canva for junior high school students in an EFL context. Employing an ADDIE-based Research and Development design, the study involved 247 eighth-grade students and two English teachers at a public junior high school in Indonesia. Data were collected through expert validation sheets, vocabulary tests, motivation questionnaires, classroom observations, and interviews. The developed materials were validated as very valid, with a mean score of 89.75%. The implementation results indicated a significant improvement in students’ vocabulary mastery, with the mean score increasing from 62.40 in the pre-test to 81.70 in the post-test. The paired-samples t-test confirmed a significant difference, t(246) = -15.62, p < .001. Students also demonstrated high learning motivation, with an overall mean score of 4.45, and motivation was strongly correlated with vocabulary achievement, r = .68, p < .01. These findings suggest that integrating multicultural content with Canva-based multimodal learning design can support meaningful, engaging, and culturally responsive vocabulary instruction. However, this study was limited to one school context and a short implementation period. Future studies are recommended to involve broader participants, longer interventions, and control-group comparisons.